Game Methods in Learning Arabic for Elementary Schools Phase A - Asep Suherman; Wido Supraha; A. Alim (al-Afkar, Journal For Islamic Studies, 2023)
Learning Arabic for phase A elementary schools in particular requires the game method as an effective medium in learning Arabic and evaluating learning Arabic. This research is the development of a game method in learning Arabic for elementary school phase A. This module is a game method that emphasizes the balance of all Arabic specific learning objectives, namely the four Arabic language skills. This game method describes the types of games based on the four Arabic skills. The development of this game method obtained a validity test score of 86% so that it has the potential to be applied in Islamic elementary schools